Innovation and location in German knowledge intensive business service firms - Stephan Brunow; Andrea Hammer-Langrock; Philip McCann (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2017)
Knowledge Intensive Business Services (KIBS) are widely perceived as being important drivers of technological progress and innovation. KIBS are generally understood as depending, driving and thriving on knowledge exchanges and therefore, geographical proximity to markets, customers and suppliers would be expected to be a critical factor in their performance. This paper investigates how the innovation performance and processes of KIBS firms are related to their distance from the nearest city and also to the size of the nearest city. For this purpose we make use of detailed firm level data and consider Germany as a research field. While most current evidence on this topic emerges from Canada, we complements and add to this existing literature on the geography of KIBS by examining these issues in the German spatial setting which largely conforms to a textbook type of spatial urban hierarchy. Our probit results indeed find that there are very strong distance decay and city size effects, and these also vary according to the innovation type. – – Wissensintensive unternehmensnahe Dienstleistungsunternehmen (KIBS) entwickelten sich als bedeutende Treiber für technologischen Wandel und Innovationen. Aufgrund der besonderen Arbeitsweise, welche auf Interaktion und Wissensaustausch aufbaut, spielt die räumliche Nähe zu Kunden, Partnern und Anbietern eine bedeutsame Rolle für die Wirtschaftlichkeit und Innovationsfähigkeit von KIBSUnternehmen. Die vorliegende Arbeit betrachtet das Innovationsverhalten in Abhängigkeit der Distanz zur nächstgelegenen Stadt und unterscheidet hierbei verschiedene Stadtgrößen. Dafür werden detaillierte Daten von deutschen KIBS-Betrieben verwendet. Die Ergebnisse indizieren, dass Distanzeffekte mit der Stadtgröße variieren und für verschiedene Innovationsarten unterschiedlich stark ausgeprägt sind. Insbesondere profitieren KIBS-Betriebe von der Nähe zu anderen Marktteilnehmern und sind besonders innovativ in Zentren. Eine gezielte Förderung von Start-Ups in Zentren erscheint daher sinnvoller als in weniger dicht besiedelten Räumen, in denen das Angebot an wissensintensiven Gütern geringer ist.
Keywords: D22; L84; O31; R12; 330; Distance decay; Innovation; KIBS; urban structure